Analysis the Effect of Enviromental Concern and Green Advertising to Green Purchasing in Palembang City - Zakaria Wahab; Rio Adistia Tama; Muchsin Saggaf Shihab; Achmad Widad; Nofiawaty Nofiawaty; Yuliansyah M. Diah (Faculty of Economics, Universitas Sriwijaya, 2017)
This study aims to determine the effect of environmental concern and green advertising to consumer behavior in purchasing green products (environmentally friendly bag). The study was conducted by distributing questionnaires to 200 respondents which already have purchase and know about new government regulations that require to buy a plastic bag that used in large retail. This study conducted in some major retail in Palembang (Hypermart, Diamond, and Carrefour). This study uses Structural Equation Modeling (SEM) with AMOS program to analyze the data. The results showed that green advertising significantly influence behavior change and environmental concerns significantly influence purchase decisions with the effect of changes in consumer behavior on purchasing decisions by 74.0 % and the balance of 26.0 % is the influence of other factors not examined in this research.